Bhabinkamtibmas Problem-Solving Authority in Student Dispute Resolution in Bandung Wetan: A Juridical Analysis Based on Restorative Justice - Mardiono Mardiono; Agus Rasyid C W (International Forum of Researchers and Lecturers, 2026)
This article examines the legal authority of Bhabinkamtibmas in resolving student disputes in Bandung Wetan through a problem-solving approach. The study employs normative juridical legal research supported by statutory, conceptual, case, and analytical approaches. The findings indicate that Bhabinkamtibmas possesses a legitimate legal basis to facilitate the settlement of community disputes under the Indonesian Constitution, Law Number 2 of 2002 concerning the Indonesian National Police, the 2015 Regulation on Community Policing, and the 2021 Police Regulation on Restorative Justice. In the context of student disputes, the problem-solving mechanism reflects the principles of restorative justice because it prioritizes dialogue, voluntary participation, social restoration, personal responsibility, deliberation, and social reintegration. This approach also seeks to prevent escalation, maintain public order, and rebuild relationships among the parties involved. However, its implementation still encounters several legal weaknesses, particularly the absence of specific regulations governing student disputes and the lack of uniform operational standards for field officers. Therefore, this article proposes a collaborative dispute-resolution model involving Bhabinkamtibmas, universities, students, and local communities. It may also improve public trust in community-based policing practices. Such collaboration is expected to strengthen legal certainty, fairness, accountability, institutional coordination, and the sustainability of dispute settlement in academic and community environments.